Islamic Educational Learning Methods - Abdul Aziz Romdhoni (Al-Fadlan: Journal of Islamic Education and Teaching, 2023)
Method of Islamic Religious Education must contain potential that directs the subject matter to the objectives of Islamic religious education to be achieved by the learning process. Educational Methodology is usually specifically related to educational objectives and materials as well as to the curriculum. Methodology in reality means efforts to achieve educational goals. In using Islamic education methods, what needs to be understood is how an educator can understand the nature of the method in its relevance to the main goal of Islamic education, namely the formation of a faithful person who is always ready to serve Allah SWT